Bad Medicine - Querry, Ronald B. (New York, NY Bantam, 1999)
In this tale of spiritualism versus science, a killer influenza strikes a Navajo reservation in Arizona. The government doctor blames a virus carried by mice, while the local health agent blames revengeful spirits. Both men are Indians.
80448
Keywords: Navajo Indians -- Fiction; Virus diseases -- Fiction; New Mexico -- Fiction